The Role of Family and Culture on Young Women’s Perceptions of Motherhood: A Comparative Study of Sri Lankan and Indian Female College Students - Kosala, L.; Jayathunga, J.T.U.; Lakshman, Iresha; Ashraf, Yasir (European Scientific Journal, ESJ, 2025)
Fertility rates in South Asia have declined significantly over the past four decades, with Sri Lanka and India leading this demographic transition. Addressing this problem, the study focuses on two key objectives: first, to explore cultural differences in the socialization process in Sri Lanka and India, particularly concerning the reinforcement of motherhood; and second, to examine culture-specific parenting practices that shape young women’s decision-making about marriage and motherhood. To achieve this, the research investigates how the socialization process of young, unmarried female undergraduates in these two countries influences their perceptions of motherhood and the declining fertility rate in contemporary times. Using a mixed-method and pseudo-longitudinal design, data were collected from over 500 students at the University of Colombo in Sri Lanka and the VET Institute of Arts and Science in Tamil Nadu, India, covering diverse academic disciplines, years of study, and socio-economic backgrounds. The findings indicate that while traditional ideals of motherhood remain deeply rooted, young women are renegotiating these roles through education, career aspirations, and exposure to global norms, though in varying ways across the two contexts. Indian students display greater confidence in balancing motherhood and career, while Sri Lankan students confront stronger patriarchal pressures and weaker institutional support. These results highlight the complex interplay of culture, family, and modern aspirations, contributing to the understanding of ongoing demographic shifts in Sri Lanka and India and offering policy-relevant insights into gender, education, and reproductive decision-making.